PROTECTIVE EFFECT OF Calotropis procera OF TOXICITY OF MERCURIC CHLORIDE VIA ROUTE OF BIOCHEMISTRY PARAMETERS - LEILA, BELFARHI; ABDELMADJID, BAIRI; IBTISSEM, CHOUBA; NAZIHA, AMRI; NADIA, BOUKRIS; ABDELKRIM, TAHRAOUI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Mercury chloride is one of the most dangerous metals for health due to its volatility and its rapidity to pass through the human body. We undertook this study with the aim of investigating the detoxification of mercury chloride by the Calotropis procera plant taken from the Algerian Sahara. In this study, the toxicity of mercury chloride affected the kidney weights of male and female rats through increased weight. On the other hand, the plant Calotropis procera demonstrated a beneficial effect by restoring the weight of the kidneys. The results of this study demonstrated that the plant Calotropis procera. procera has a beneficial effect on the liver, which was able to restore its weight affected by the mercury chloride. Treatment of male and female rats with mercury chloride has also been found to lower blood urea levels, uric acid, proteins total, alkaline phosphatase and direct, indirect, total bilirubin levels. This toxicant caused an increase in blood sugar levels, blood creatinine, in male and female rats. Our results demonstrated no effect of mercury chloride and of the plant on cholesterol levels and triglycerides in female rats. No change in albumin levels was found in male and female rats. However, mercury chloride was found to increase cholesterol and triglyceride levels in male rats. The Calotropis procera plant restored cholesterol and triglycerides in male rats. This study can help to clarify that the detoxification of mercury chloride by Calotropis procera act directly on liver and kidney by ameliorating uric acid, blood sugar, creatinine, albumin, alkaline phosphatase, urea, total protein.